Aprendizagem docente no contexto da alfabetização: movimentos formativos de professoras a partir da tríade ensino, pesquisa e extensão - Millani, Silvana Martins de Freitas (2012)
This study is part of the research area Formação, Saberes e Desenvolvimento Profissional (Formation, Knowledge and Professional Development) of the Post-Graduation Program in Education of Universidade Federal de Santa Maria. The objective of this study is to understand which formation movements are produced by teachers from their involvement in the triad teaching, research and extension and how they reverberate in the teacher s learning in the literacy context. Thus, we considered the theoretical presuppositions of authors such as Leontiev (1984, 2006), Davidov e Márkova (1987), Nóvoa (1991, 1992), Zeichner (1993), Vygotski (1995, 1997, 2001, 2006), Schön (1997), Marcelo Garcia (1999), Ferreiro (1999, 2010), Bolzan (2002, 2009), Isaia (2006, 2008), Tardif (2006), among others. In this sense, we developed this research based on the qualitative approach of sociocultural nature and the studies of Bakthin (1986), Vygotski (2001), Bolzan (2002), Freitas (2002). We considered that this methodological approach makes possible the approximation with contexts and experiences narrated by the teachers, establishing, therefore, a dialogical and reflexive relation which forms and transforms itself based on the personal and professional story of each individual. Hence, we established as instruments for data collection the semi-structured interview through the use of guide-topics, which were later registered based on the recordings and transcriptions. For the development of the interview, four teachers members of the activities of teaching, research and extension of a research group of Universidade Federal de Santa Maria collaborated, narrating their experiences with these activities in the classroom. The analysis of these interviews was organized since the narrative recurrence which indicated the construction of the categories of research. Thus, it was possible to ellaborate three categories which comprise the indicative elements of the formative movements of the teachers and their repercussion in the learning of teachers who work with literacy: the teacher s reflexive learning; the teacher s study activity and the pedagogical autonomy. We considered, yet, that these categories are developed in an inter-related way and are impelled by two formative movements: the self-formation and the interformation. This way, they represent a spiral movement which re-does and extends itself every new learning, promoting the teachers professional development with personal and interpersonal formative activities. This process is permeated by three transversal elements: the pedagogical practice, the reflexive activity and the collaborative activity which configure themselves as activities which constitute the dynamics of production in the teachers study activity since the development of the triad teaching, research and extension. We understand, therefore, that this formative dynamics reverberates in a positive way in the learning of teachers who work with literacy once it makes possible to teachers the appropriation and production of knowledge and activities related to the process of construction of reading and writing.